Relato de estágio curricular obrigatório: área de anestesiologia veterinária - Susin, Isabella Mitteregger (My University, 2026)
The mandatory curricular internship was carried out at the university veterinary hospital, belonging to the Federal University of Santa Maria, in the area of veterinary anesthesiology. It was supervised by Professor Karina Affeldt Guterres, PhD, and supervised by Veterinarian Beatriz Perez Floriano, and took place from August 4 to October 17, 2025, totaling 509 hours. During this period, 95 animals were treated, with a focus on dogs (75.5%), mainly ASA III animals (42.9%). During the internship, most of the anesthetic protocols monitored consisted of partial intravenous anesthesia, used in 50% of cases. It was also observed that 38.75% of the animals did not receive pre-anesthetic medication. Regarding anesthetic induction, 24.43% of the protocols used propofol, and 15.91% of the cases used continuous infusions with a combination of fentanyl, lidocaine, and ketamine. In addition, 56.67% of patients received supportive therapy consisting of meloxicam, dipyrone, and cephalothin. The objective of this report is to describe the internship location, activities, and cases treated, as well as to report two cases followed during the period. The first refers to the anesthetic management of a Shih Tzu dog with hypoadrenocorticism undergoing pulmonary lobectomy due to pulmonary adenocarcinoma, and the second refers to the anesthetic aspects of patent ductus arteriosus (PDA) occlusion in a German Spitz dog. [resumo fornecido pelo autor]
O estágio curricular obrigatório foi realizado no hospital veterinário universitário, pertencente à Universidade Federal de Santa Maria, na área de anestesiologia veterinária. Foi orientado pela Professora Doutora Karina Affeldt Guterres e supervisionado pela Médica Veterinária Beatriz Perez Floriano, sendo realizado no período de 04 de agosto a 17 de outubro de 2025, totalizando 509 horas. Neste período foram atendidos 95 animais, com destaque na espécie canina (75,5%), principalmente animais em ASA III (42,9%). Durante o estágio, a maior parte dos protocolos anestésicos acompanhados consistiu em anestesia parcialmente intravenosa, utilizada em 50% dos casos, observou-se também que 38,75% dos animais não receberam medicação pré anestésica, em relação à indução anestésica, 24,43% dos protocolos empregaram propofol e 15,91% dos casos utilizaram infusões contínuas com a combinação de fentanil, lidocaína e cetamina. Além disso, 56,67% dos pacientes receberam terapia de suporte composta por meloxicam, dipirona e cefalotina.O objetivo deste relatório é descrever o local de estágio, as atividades e casuísticas atendidas, assim como relatar dois casos acompanhados durante o período. O primeiro se refere ao manejo anestésico em canino Shih Tzu, com hipoadrenocorticistmo submetido à lobectomia pulmonar devido à adenocarcinoma pulmonar e o segundo sobre os aspectos anestésicos da oclusão da persistência de ducto arterioso (PDA) em um canino, Spitz Alemão. [resumo fornecido pelo autor]
Keywords: Medicina veterinária; Hospitais veterinários; Centros cirúrgicos; Anestesiologia; Pneumonectomia - Estudo de caso